Glycemic Control Among Type 2 Diabetics: Comparison of Patients Coming to Specialized Clinics vs General Clinics for Diabetes - Khawar Hussain Qureshi, Syed Hasan Danish, Farah Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To analyze the difference of glycemic control (Mean HBA1c) between patients consulting at specialized Diabetic clinic and those coming to usual general practices. Study Design: Quasi Experimental study Place and Duration: OPDs of general Practice clinics and Outpatient department of a specialized diabetes clinic at Sialkot for 3 months. Methodology: Total n=250 patients were inducted using consecutive sampling technique carried for 3 months. The sample was divided into two groups “Diabetes Specialist clinics” (n=125) and with traditional setup without a team approach as “general practice clinics” (n=125).In this study patients included were of both gender with age group comprising > 40 years and history of T2Dm for at least one year. Type1 dm, gestational diabetes and those without signing consent were excluded. Data was collected using structured questionnaire by primary investigator after informed consent and at the end of three months the difference of means of HBa1c of two different groups. Analysis was done on SPSS version 22 using independent sample t-test. Mean and standard deviation were taken for numerical data, while for categorical data, percentages and frequency were taken out. Statistically significant p value was viewed as < 0.05. Results: When Independent T Test was applied, in specialist clinic HBA1c was 8.51±1.23 whereas in General practice clinic it was 9.57±1.62 with statistically significant difference (p value 0.000). When ANOVA applied to see differences in HBA1c among those with primary, secondary, Intermediate and graduate level education, statistically insignificant results were found (p value 0.373). Likewise, when compared by duration of diabetes, statistically insignificant results were found (p value 0.379). Results were statistically insignificant (p value 0.95), when compared based on rural and urban residence. Conclusion: The study shows statistically significant difference in glycemic control (HBA1c) levels between those coming to general practice clinics and those consulting at specialized diabetic clinics. Keywords: Diabetes, Diabetes Specialist clinic, HbA1C